Epilepsy: a comprehensive textbook - Engel, Jerome; Moshé, Solomon L. (Wolters Kluwer, 2024)
"Authoritative and updated, Epilepsy: A Comprehensive Textbook, 3rd Edition, contains 365 chapters that cover the full spectrum of relevant topics in biology, physiology, and clinical information, from molecular biology to public health concerns in developing countries. Written by world-renowned authorities and expertly edited by epileptologists Drs. Jerome Engel, Jr., Solomon L. Moshé, Aristea S. Galanopoulou, John M. Stern, Alexis Arzimanoglou, Jacqueline A. French, Renzo Guerrini, Andres M. Kanner, and Istvan Mody, this three-volume work includes detailed discussions of seizure types and epilepsy syndromes, relationships between physiology and clinical events, psychiatric and medical comorbidities, conditions that could be mistaken for epilepsy, and an increasing range of pharmacologic, surgical, and alternative therapies"--